Health-Related Quality of Life, Blood Pressure, and Biochemical and Anthropometric Profile in Vegetarians and Nonvegetarians - Jacksaint Saintila; Tabita E. Lozano López; Percy G. Ruiz Mamani; Michael White; Salomón Huancahuire-Vega (Journal of Nutrition and Metabolism)
Several studies have been carried out which mainly focus on the analysis of the lipid profile in vegetarians and nonvegetarians. However, few studies have been undertaken in this population oriented to quality of life and health. This study aimed to compare health-related quality of life, blood pressure, and biochemical and anthropometric profile in vegetarians and nonvegetarians. The study included 149 participants out of an initial sample of 162: 62 vegetarians and 87 nonvegetarians. Health-related quality of life was assessed with the SF-12 Health Questionnaire version 2 and was related with the lipid profile, glucose, blood pressure, anthropometric measures, and sociodemographic characteristics. Vegetarians presented better Body Mass Index (BMI) and waist circumference (WC), as well as higher LDL levels. No significant differences in HDL and TG concentrations were found. Serum glucose concentrations were significantly lower among vegetarians. Nonvegetarian males had higher diastolic pressure levels. Vegetarian women had significantly higher levels of systolic pressure. As for the physical health and mental health components of quality of life, no significant differences were found in vegetarian and nonvegetarian women and men. In conclusion, vegetarians presented a better anthropometric profile, lower glycaemia, and higher LDL levels but no significant differences in health-related quality of life compared with nonvegetarians.